Regulation of Capitalization and Supervision in the General Insurance Industry: a Comparative Analysis of Indonesia and Hong Kong - Citra Pusparini; Antonius Anton Lie; Ari Widiatmoko (Return : Study of Management, Economic and Bussines, 2026)
This article presents a comparative analysis of capital regulation and supervision in the general insurance sector in Indonesia and Hong Kong, and assesses their implications for industry resilience and policyholder protection. The study employs a comparative qualitative design, combining document analysis of key regulations (POJK, UU P2SK, HKRBC, HKIA guidelines) and semi-structured interviews with regulators, industry players, and experts, which are then analyzed thematically using a comparison matrix. Indonesia has strengthened industry resilience primarily through gradual increases in minimum nominal capital and market consolidation, while Hong Kong relies on the Hong Kong Risk-Based Capital (HKRBC) framework that links capital requirements directly to each company's risk profile. In terms of supervision, the Financial Services Authority (OJK) implements Risk-Based Supervision (RBS), which is still in the capacity-building phase, while the Hong Kong Insurance Authority (HKIA) has integrated the three pillars of HKRBC—quantitative capital, Enterprise Risk Management (ERM) and governance, and disclosure—into its mature risk-based and group-wide supervision regime. The study concludes that systematically strengthening the capital and supervisory frameworks in both jurisdictions adds layers of protection and improves governance, but also requires structural readiness, quality human resources, and adaptability at both the firm and regulatory levels. Key lessons from Hong Kong for Indonesia include the need for a clear roadmap to a deeper risk-based regime, strengthening ERM and key governance functions, and leveraging data and interagency collaboration to support effective and sustainable supervision.